2019
DOI: 10.1016/j.kint.2018.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trajectory of kidney function in autosomal-dominant polycystic kidney disease

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is characterized by cyst and kidney growth, which is hypothesized to cause loss of functioning renal mass and eventually end-stage kidney disease. However, the time course of decline in glomerular filtration rate (GFR) is poorly defined. The Consortium for Radiologic Imaging Studies of Polycystic Kidney Disease study is a 14-year observational cohort study of 241 adults with ADPKD. As an estimate of the rate of kidney growth, participants were stratified int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 29 publications
(49 reference statements)
7
54
2
Order By: Relevance
“…Although children with very-early-onset ADPKD have poorer outcomes 89 , no studies have examined whether the prediction of 'rapid progressors' by repeated imaging in children is feasible and clinically helpful. Our recommendation (Box 6) would change in the future if paediatric studies show a predictive value of kidney imaging on later progression to end-stage renal disease (ESRD; as has been shown in adults 90 ) and a treatment to slow disease progression is licensed specifically for children who are at risk of early progression to ESRD.…”
Section: Routine Monitoring Of Cyst Growthmentioning
confidence: 99%
“…Although children with very-early-onset ADPKD have poorer outcomes 89 , no studies have examined whether the prediction of 'rapid progressors' by repeated imaging in children is feasible and clinically helpful. Our recommendation (Box 6) would change in the future if paediatric studies show a predictive value of kidney imaging on later progression to end-stage renal disease (ESRD; as has been shown in adults 90 ) and a treatment to slow disease progression is licensed specifically for children who are at risk of early progression to ESRD.…”
Section: Routine Monitoring Of Cyst Growthmentioning
confidence: 99%
“…An increase in TKV is widely accepted as being the dominant feature of ADPKD progression, as TKV www.nature.com/scientificreports www.nature.com/scientificreports/ is inherently linked to the pathogenesis of PKD and represents a primary event rather than a secondary consequence of disease-causing mutations 21 . Indeed, it was recently demonstrated that the proportion of the total effect of gene type that is mediated by Mayo class is 0.73, supporting the notion that PKD mutations cause loss of GFR predominantly by affecting kidney size 17 . A htTKV ≥600 mL/m at baseline predicts the development of stage 3 CKD within 8 years 22 , and patients with higher rates of TKV growth at baseline have an increased frequency of ESRD after 10 years 16 .…”
Section: Discussionmentioning
confidence: 84%
“…An analysis of CD subjects by reason for diagnosis (subjects diagnosed due to symptoms and other subjects) showed a significant difference between observed and predicted eGFR for tolvaptan-treated subjects but not placebo-treated subjects, possibly due to the small analysis population (Supplementary Table 10). Finally, a sensitivity analysis based on the mixed polynomial prediction model developed by Yu et al 17 found no significant differences in observed versus predicted eGFR in either tolvaptan-or placebo-treated subjects defined by age at diagnosis (Supplementary Table 11).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations